AGROECOLOGICAL ASSESSMENT OF USE OF HERBICIDES IN THE VINEYARDS OF AZERBAIJAN REPUBLIC - Гаджієва Є. А., (World of Medicine and Biology, 2016)
Selecting the correct species composition of weeds and herbicides in the vineyards, it is necessary to conduct a chemical fight to the end of vegetation correctly obeying the rules of herbicides. At the period of application of chemical struggle together with the reduction of environmental risks increase the yield of grapes to a large extent. Together with increased productivity and profitability.
Keywords: vineyards; weeds; herbicides; ecology; agrocenosis; useful fauna; feeding regime; microflora; the residual amount; yield